Copper/Zinc Superoxide Dismutase from the Crocodile Icefish Chionodraco hamatus: Antioxidant Defense at Constant Sub-Zero Temperature - Evangelia Chatzidimitriou; Paola Bisaccia; Francesca Corrà; Marco Bonato; Paola Irato; Laura Manuto; Stefano Toppo; Rigers Bakiu; Gianfranco Santovito (MDPI AG, 2020)
In the present study, we describe the purification and molecular characterization of Cu,Zn superoxide dismutase (SOD) from Chionodraco hamatus, an Antarctic teleost widely distributed in many areas of the Ross Sea that plays a pivotal role in the Antarctic food chain. The primary sequence was obtained using biochemical and molecular biology approaches and compared with Cu,Zn SODs from other organisms. Multiple sequence alignment using the amino acid sequence revealed that Cu,Zn SOD showed considerable sequence similarity with its orthologues from various vertebrate species, but also some specific substitutions directly linked to cold adaptation. Phylogenetic analyses presented the monophyletic status of Antartic Teleostei among the Perciformes, confirming the erratic differentiation of these proteins and concurring with the theory of the "unclock-like" behavior of Cu,Zn SOD evolution. Expression of C. hamatus Cu,Zn SOD at both the mRNA and protein levels were analyzed in various tissues, highlighting the regulation of gene expression related to environmental stress conditions and also animal physiology. The data presented are the first on the antioxidant enzymes of a fish belonging to the Channichthyidae family and represent an important starting point in understanding the antioxidant systems of these organisms that are subject to constant risk of oxidative stress.